A Study to Analyze the willingness of Smokers to Quit Smoking Following Dentist’s Advice - Vishwas Mishra; Shitanshu Malhotra; Madhusudan Krishna; Manu Narayan (Institute of Medico-legal Publications Pvt Ltd, 2021)
Aim: To analyze the patient’s perceptions about the role of dentists in smoking prevention, counseling andcessation and to analyze the willingness of smokers to quit smoking following dentist’s advice.Materials and Methods: A descriptive study was conducted among dental patients visiting Dental Collegeand Hospital in the month of November 2019 using a self administered questionnaire. Convenient samplingwas done. Among five hundred patients who participated in the study, 486 completed it with a response rateof 97.2%. The descriptive statistics and chi square analysis was performed to analyze data.Results: The patients had good knowledge about the effects of smoking on general and oral health. Howeverits effect on hair loss, ageing and wound healing can be reinforced. Non smokers had significantly higher(p<0.05) knowledge about the effects of smoking on ageing, bad breath, gum diseases and oral cancercompared to smokers. Patients had positive perception about the role of dentist in smoking cessationactivities. Smokers exhibited willingness to quit if suggested by the dentist.Conclusion: Patients perceive that dentists can play an important part in smoking cessation activities. Hencedentists should not hesitate to give smoking advice to their patients and grasp this opportunity to improve thegeneral and oral health of the community.